2009
DOI: 10.1021/np9004135
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Elucidation of Euryjanicins B−D, Proline-Containing Cycloheptapeptides from the Caribbean Marine Sponge Prosuberites laughlini

Abstract: Three new cyclic peptides, euryjanicins B (2), C (3), and D (4), have been isolated from the Puerto Rican marine sponge Prosuberites laughlini, and the structures were elucidated by chemical degradation, ESIMS/MS, and extensive 2D NMR methods. When tested against the National Cancer Institute 60 tumor cell line panel, all of the purified isolates displayed weak cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
3
16
0
2
Order By: Relevance
“…Some of them are used in the clinic, e.g., gramicidin S and tyrocidine with bactericidal activity, while others are in clinical trials, e.g., dehydrodidemnin B, and most of them originate from natural resources. Although the literature is enriched with reports concerned with marine-derived linear proline-rich bioactive peptides [1,2,3,4,5], e.g., dolastatin 15, kurahyne B, jahanyne, cemadotin, koshikamide A 1 , etc., PRCPs from marine resources are becoming popular and attracting the attention of scientists nowadays, due to their unique structural features and a wide range of the biological properties, like cytotoxicity [6], antibacterial activity [7], antifungal activity [8], immunosuppressive activity [9], anti-inflammatory activity [10], anti-HIV activity [11], repellent (antifouling) activity [12], antitubercular activity [13] and antiviral activity [14], associated with them. PRCPs include a large and heterogeneous group of small to large-sized oligopeptides characterized by the presence of proline units often constituting peculiar sequences, which confers them a typical structure that determines the various biological functions endowed by these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are used in the clinic, e.g., gramicidin S and tyrocidine with bactericidal activity, while others are in clinical trials, e.g., dehydrodidemnin B, and most of them originate from natural resources. Although the literature is enriched with reports concerned with marine-derived linear proline-rich bioactive peptides [1,2,3,4,5], e.g., dolastatin 15, kurahyne B, jahanyne, cemadotin, koshikamide A 1 , etc., PRCPs from marine resources are becoming popular and attracting the attention of scientists nowadays, due to their unique structural features and a wide range of the biological properties, like cytotoxicity [6], antibacterial activity [7], antifungal activity [8], immunosuppressive activity [9], anti-inflammatory activity [10], anti-HIV activity [11], repellent (antifouling) activity [12], antitubercular activity [13] and antiviral activity [14], associated with them. PRCPs include a large and heterogeneous group of small to large-sized oligopeptides characterized by the presence of proline units often constituting peculiar sequences, which confers them a typical structure that determines the various biological functions endowed by these molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other natural proline-rich cyclooligopeptides isolated from marine sponges which contain either two ‘Pro’ units adjacent to each other (e.g., hymenistatin 1, euryjanicin B [61,62]) or separated from each other by amino acid units such as tryptophan, histidine, serine or asparagine in the cyclic chain (e.g., stylissamide H, wainunamide, dominicin, axinellin A [19,63,64,65]), stylissamide G has a characteristic pattern of two ‘Pro’ units separated by one ‘Phe’ unit in a repeated manner in its structure. It is found to be associated with antibacterial, antifungal and anthelmintic effects, as supported by previous literature reports [5] involving cyclic peptide, viz.…”
Section: Discussionmentioning
confidence: 99%
“…Two lyophilized extracts of cycloheptapeptides from the Caribbean Marine Sponge Prosuberites laughlini were found to show two distinct biological activities. The EtOAc fraction with substances of a peptidic nature retained most of the original antitumor activity without anti-TB activity while the n-BuOH extract, mainly comprised of a mixture of the pyrrole alkaloids monobromoisophakellin (7a) and hymenidin (7b), was strongly antitubercular but weakly cytotoxic [38]. Preliminary tests for anti-TB activity of the alkaloids 7a and 7b demonstrated that these compounds significantly inhibited the growth of Mtb H 37 Rv with MIC values of 6.1 and 64.0 μg/mL, respectively [39].…”
Section: Newly Reported Anti-tb Natural Products From 2009 To Presentmentioning
confidence: 99%
“…Their activity data suggest that stereochemical interconversion of 36 and 37 affect their reactivity and bioactivity. CGI-17341 (38) is the lead compound in the nitroimidazole series shown in Fig. (8).…”
Section: Some Cases Showing the Importance Of Stereochemistry In Semimentioning
confidence: 99%